PENGARUH LITERASI HALAL DAN RELIGIUSITAS TERHADAP MINAT KONSUMSI PRODUK HALAL MASYARAKAT KABUPATEN MADIUN - Anis Setyowati; Moch. Khoirul Anwar (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2022)
Along with the increasing circulation of halal products on the Indonesian market, which causes an increase in public interest in consuming halal products, there are several influencing factors. This study will discuss the effect of halal literacy and religiosity on interest in consuming halal products, a case study of Madiun Regency. The method used is quantitative. The type of research data used is primary research data by distributing questionnaires in the form of Google Forms to the people of Madiun Regency with 100 respondents. Data processing to accurate results using instrument tests consisting of validity and reliability tests, classical assumption test, multiple linear regression analysis, t-test, f-test, and the coefficient of determination (R2) test. The results showed that halal literacy and religiosity partially and simultaneously influence the interest in consuming halal products in Madiun Regency for a contribution role of 42.8%.